(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article outlines the methodology for conducting laboratory investigations into the effects of hydrogen on reservoir rocks. It details the stages of sample analysis and the instruments employed during the experiments. A comparative evaluation of the porosity and permeability of core samples was undertaken, revealing a 4.6% decrease in porosity and a 7.9% reduction in permeability following hydrogen exposure. Correlation analysis indicated a typical shift in the relationship between these characteristics: post-exposure, the variability of values increased while the correlation coefficient decreased, suggesting alterations in the void structure. The findings suggest that the observed reductions in porosity and permeability are attributed to slight compaction due to effective stresses. Chemical analyses indicated no significant changes in the composition of primary oxides before and.